Microplastics in urban soils of Nanjing in eastern China: Occurrence, relationships, and sources. (September 2022) - Zhou, Yujie; Wang, Junxiao; Zou, Mengmeng; Yin, Qiqi; Qiu, Yifei; Li, Chengqiang; Ye, Bei; Guo, Tianwei; Jia, Zhenyi; Li, Yan; Wang, Chunhui; Zhou, Shenglu
Abstract: Although microplastic (MP) pollution has been defined as a new global challenge by the United Nations Environment Programme, their abundance and composition has only been studied in-depth within farmland soil, while minimal attention has been placed on urban soil contamination. Accordingly, within the current study, MP abundance and composition is investigated within urban soil from green spaces in Nanjing, eastern China. The average MP abundance in soil was 461 ± 222 items/kg and primarily comprised fibers (39.1%) and fragments (37.7%). MPs <1000 μm in size accounted for 83.7% of the total content and white MPs were the most abundant (26.5%). The dominant polymers were polyethylene glycol terephthalate (32.0%) and polypropylene (20.5%). Moreover, relationship network analysis generated three distinct MP modules based on community similarity. Indeed, the degree of similarity increased by ∼26.8% per kilometer. Furthermore, application of a forward selective optimal multiple regression model identified clay, sand, longitude, and points of interest for recycling bins (RecyclePOI) as the primary spatial and soil environmental factors affecting MP abundance and composition. Additionally, five potential sources of MPs were identified based on the MP diversity integrated index fitting results, and point of interest density (MDII-POI) source analysis ( R 2  = 0.21–0.62; P  < 0.05). In particular, the point of interest of express delivery points (ExpressPOI) were important sources of plastic emissions as they are widely distributed throughout urban and fringe areas. Collectively, the findings of this study provide novel insights regarding quantitative source appointment and regional ecological control of MPs in urban soil. Graphical abstract: Image 1 Highlights: MP pollution of urban soil in Nanjing was investigated for the first time. Relationship networks revealed the difference and modularity of MP communities. Occurrence of MPs was result of interactions between source-sink factors. Five types of sources were isolated based on MDII-POI source appointment.